Two new Cd(II)/Zn(II) coordination polymers: luminescence properties and synergistic treatment activity with ultrasound therapy on uterine fibroids. Issue 1 (31st December 2022) - Liu, Hong-Mei; Shang, Xiao-Na
ABSTRACT: Through the self-assembly reaction of 5-substituted isophthalic acid and bis(imidazolyl) ligands with Cd(II) ion or Zn(II) ion, two new coordination polymers with the chemical formulae of [Cd(5-meo-ip)(bmip)]n (1 ) and [Zn(5-pro-ip)(bip)]n ·2 n(H2 O) (2 ) (5-meo-H2 ip = 5-methoxyisophthalic acid, 5-pro-H2 ip = 5-propoxyisophthalic acid, bmip = 1, 3-bis(2-methylimidazolyl)propane bip = 1, 3-bis(imidazolyl)propane) were successfully obtained and structurally characterized by a series of characterization techniques. Moreover, compounds 1 –2 show intense blue luminescence at room temperature. Furthermore, the assessment of their treatment activity on the uterine fibroids combined with ultrasound therapy was evaluated and the specific mechanism was investigated at the same time. Firstly, the effect of compound treatment on uterine fibroids apoptosis was detected via flow cytometry. Next, the apoptotic signaling pathway activation was detected through the Caspase-3 and Caspase-8 Activity Assay Kit.